Sistem Pakar Klasifikasi Siswa Tunagrahita Pada SLB Shanti Yoga Klaten Menggunakan Metode Naive Bayes - Rousyati Universitas BSI PSDKU bandung; Noor Hasan Universitas BSI PSDKU Yogyakarta (SPEED - Sentra Penelitian Engineering dan Edukasi, 2018)
Abstract - SLB Shanti Yoga is one of the schools with special needs for the mentally retarded in Klaten. The teachers at the school experienced problems in classifying mentally retarded students to determine the class to be occupied. In determining the class adjusted to the mental retardation classification which consists of three levels, namely mild mental retardation, moderate intellectual disability, and severe mental retardation. To determine the level of mental retardation classification in students requires a diagnosis from an expert who is a psychologist and psychiatrist. But the Shanti Yoga Special School does not provide experts. Based on these problems, the authors make the title of the thesis "Expert System for Classification of Mentally Retarded Students in the SLB Shanti Yoga Klaten Using the Naive Bayes Method". The Naive Bayes method is used by the author to calculate the probability and statistics of 135 student data in the SLB Shanti Yoga Klaten regarding the symptoms that arise. The purpose of building an expert system in classifying mentally retarded students is to diagnose whether students who study at the Shanti Yoga SLB include mild, moderate or severe mental retardation because each class occupies a different class. Based on the tests made, the Naive Bayes method can be used to assist calculations in the classification system of mentally disabled students. This is evidenced by the assessment of classification of mentally retarded students which is more appropriate because it is based on the symptoms that arise that are needed in this study.Keywords: Expert System, Mentally Disabled Student Classification, Naive Bayes